The Power of Perspective in The Raven Cycle - Dumančić, Andrea; Oklopčić, Biljana (Anafora, 2023)
Beginning with the discussion of the terms narration and narrative, the paper asserts the difference between point of view, which is defined as “who” tells a story, and perspective, which shows “how” a narrator / a character perceives the events making up the story. To show the power of perspective in a literary work, the paper focuses on the young adult novel series The Raven Cycle by Maggie Stiefvater. The five main characters – Blue Sargent, Richard Gansey III, Adam Parrish, Ronan Lynch, and Noah Czerny – have been given unique perspectives that are unveiled through their separate character arcs. Blue’s perspective is clad with assumptions; Gansey’s is a clash between the perceived and the perceiving; Adam’s comes to light only when compared to other characters’ perspectives; Ronan’s is postponed and contrary to expectations; Noah’s is absent until the very end of the series.